Tren Penelitian Modul Elektronik Ekonomi: Analisis Bibliometrik - Annisa Yulistya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The change from the Industrial Revolution 4.0 era to Society 5.0 has had a significant impact on education, especially through the use of technology in the learning process. The use of electronic modules, which combine text, audio, images, animation, and video, is one of the important innovations that supports 21st century learning with a focus on critical thinking, communication, collaboration, and creativity. This study uses bibliometric analysis to examine the trends and developments of electronic modules in economics learning from 2015 to 2024. The results of the study indicate that electronic modules increase students' independence and critical thinking skills and support more interactive and flexible learning. Bibliometric analysis conducted with VOSviewer identified research trends, topic relevance, and potential for further development. Electronic modules have proven to be an effective tool in digital education, although there are still some limitations in accessibility and interactivity. These findings emphasize the importance of innovation and continuous development of electronic modules in economics education to meet the needs of learning in the digital era.